Educational programs in Andalusia promoting linguistic skills - Santos-Díaz, Inmaculada Clotilde (My University, 2016)
The Organic Law 2/2006, of 3rd of May, and the Organic Law 8/2013, of 9th December, for the Improvement of Quality in Education (LOMCE) establish the importance of reading as a quality education factor. The Andalusian Government promoted, under the Instructions of 30th of June 2013, the implementation of linguistic programs in order to encourage and support global projects based on the linguistic communication improvement (including non-linguistic subjects) focusing on reading, creativity, writing and multiple literacies. This paper aims to present linguistic programs and projects implemented in Andalusia as a way of sharing good teaching practices. Programs are divided in two groups according to level of participation of teachers. On the one hand, the only program of level 1 is the School Language Project. It requires the participation of 50 % of teachers and it promotes the educational innovation in order to build a linguistic project that will take part in the annual plan of the centre (including all areas). It is also linked to the integrated language curriculum that tries to implement the same structure and strands for Spanish as a mother tongue and English and French as foreign languages. On the other hand, level 2 programs required the participation of 10 % of teachers of an educational centre. These are: Classic Readings, Reading Families, Literary Creativity and Communication. Each program contains a syllabus with different activities and a collaborative space with a specialised community of teachers that are available on line (Portal de Lectura de la Junta de Andalucía). Examples of good teaching practices and projects will be shown during the paper to assess teachers of all areas and to be taken as a referee in other regions and countries.
Keywords: Lectura - Estudio y enseñanza; Programa educativo; Competencias lingüísitcas; Recursos educativos